Perceptions of Desired Core Competencies Among Korean College Students: A Q Methodology Study - Yu Cheon Kim; Song Yi Lee (SAGE Open)
Competency development is critical for college students to prepare for future careers after graduation. A scientific investigation of these students’ perceptions of competency can help develop effective ways to enhance their competencies. This study used Q methodology, which reveals subjectivity, to examine Korean college students’ perceptions of the core competencies they seek to improve and their corresponding reasons. The study participants included 49 students at a university in South Korea. The researchers explained the study’s purpose to the participants, obtained consent, and performed Q sorting. The study derived four types of students: Type 1 preferred improving personal competencies through professional development, Type 2 desired improving character development, Type 3 selected improving adaptability, and Type 4 favored improving cooperation. This study explored the perception types to determine how to enhance competencies for student success after graduation.